Kegiatan peduli anak stunting (PEDAS) dengan pemenuhan gizi dari bahan pangan lokal - Anggunan, Anggunan; Fransiska, Amelia; Hanafi, Ari Eka; Septiani, Ayu Aulia; Indriana, Danti; Gunawan, Muhammad Arfan; Putra, Ramanda Hadi; Maharani, Reysha Putri; Syahrin, Tiara Laili Alfy (JOURNAL of Public Health Concerns, 2025)
Background: Stunting is a condition of growth failure in toddlers due to chronic malnutrition and frequent recurrent infections, especially during the first 1,000 days of life. Stunting is characterized by a child's height being lower than the standard for their age. The impact is not only physical, but also cognitive development and future productivity. Stunting remains a significant health problem in Negara Batin Village, West Kota Agung District, Tanggamus Regency. This condition is closely related to the community's lack of understanding regarding balanced nutrition, parenting practices, and environmental health. Purpose: To increase community knowledge about stunting prevention through nutrition education and nutritious food processing practices based on local ingredients. Method: The "Caring for Stunting Children" outreach activity was held at the Negara Batin Village Hall, West Kota Agung District, Tanggamus, on August 12, 2025, from 8:00 a.m. to close. Forty-one participants attended, consisting of pregnant women and mothers of toddlers from the Negara Batin Village community. The delivery of material in this extension activity uses an interactive method through open discussions and question and answer sessions with the participants. Results: The community demonstrated high enthusiasm and active participation in the discussion sessions. Prior to the activity, most residents did not fully understand the causes and prevention of stunting. Using corn as the main ingredient in porridge also provides added value. Besides being readily available, corn boasts excellent nutritional value for children, making it a healthy food alternative. Conclusion: The "Caring for Stunting Children" outreach program had a positive impact on the community. Through education and hands-on practice, participants were able to effectively increase their understanding of balanced nutrition, parenting styles, and environmental health. Suggestion: The community of Negara Batin Village is expected to be more concerned with stunting prevention by maintaining a nutritious diet, good parenting styles, and environmental cleanliness. Village officials and health workers need to continue providing regular education and supporting facilities to ensure the sustainability of these efforts. Keywords: Balanced nutrition; Local food ingredients; Outreach; Stunting prevention Pendahuluan: Stunting adalah kondisi gagal tumbuh pada anak balita akibat kekurangan gizi kronis dan sering mengalami infeksi berulang, terutama pada 1.000 hari pertama kehidupan. Stunting ditandai dengan tinggi badan anak yang lebih rendah dari standar usianya. Dampaknya bukan hanya pada fisik, tetapi juga perkembangan kognitif dan produktivitas di masa depan. Stunting masih menjadi masalah kesehatan yang cukup menonjol di Pekon Negara Batin, Kecamatan Kota Agung Barat, Kabupaten Tanggamus. Kondisi ini erat kaitannya dengan kurangnya pemahaman masyarakat mengenai gizi seimbang, pola asuh anak, serta kesehatan lingkungan. Tujuan: Untuk meningkatkan pengetahuan masyarakat tentang pencegahan stunting melalui edukasi gizi dan praktik pengolahan makanan bergizi berbasis bahan lokal. Metode: Kegiatan penyuluhan “Peduli Anak Stunting (PEDAS)” dilaksanakan di Balai Pekon Negara Batin, Kecamatan Kota Agung Barat, Tanggamus pada tanggal 12 agustus 2025 pukul 08.00 – selesai WIB. Partisipan yang hadir dalam acara ini sebanyak 41 peserta yang terdiri dari ibu hamil dan ibu yang mempunyai balita merupakan warga Pekon Negara Batin. Penyampaian materi dalam kegiatan penyuluhan ini menggunakan metode interaktif melalui diskusi terbuka serta sesi tanya jawab bersama para peserta. Hasil: Masyarakat menunjukkan antusiasme yang tinggi dengan keterlibatan aktif dalam sesi diskusi. Sebelum kegiatan, sebagian besar warga belum memahami secara detail mengenai faktor penyebab dan cara pencegahan stunting. Pemanfaatan jagung sebagai bahan pangan utama bubur juga memberikan nilai tambah. Selain mudah diperoleh, jagung memiliki kandungan gizi yang baik bagi anak, sehingga dapat dijadikan alternatif makanan sehat. Simpulan: Kegiatan dengan program penyuluhan “Peduli Anak Stunting (PEDAS)”) memberikan dampak positif pada masyarakat. Melalui edukasi dan praktik langsung secara efektif dapat meningkatkan pemahaman peserta mengenai gizi seimbang, pola pengasuhan, serta kesehatan lingkungan. Saran: Masyarakat Pekon Negara Batin diharapkan lebih peduli terhadap pencegahan stunting dengan menjaga pola makan bergizi, pola asuh yang baik, serta kebersihan lingkungan, sementara perangkat desa dan tenaga kesehatan perlu terus melakukan edukasi secara berkala dan menyediakan fasilitas pendukung agar upaya ini berjalan berkelanjutan.